Earthquakes [electronic resource] : plate tectonics and earthquake hazards - Kusky, Timothy M. (Hazardous Earth, 2008)
"Explores the furious impact of nature and the massive devastation that is often the result of the relentless forces built up within the Earth"--P. [4] of cover.